Analysis of the relationship between food role models and nutritional status of toddlers among working mothers in Yogyakarta - Sari, Annisa Nurdiana; Fauzia, Faurina Risca; Mahfida, Silvi Lailatul; Solichah, Kurnia Mar’atus (Jurnal Cakrawala Promkes, 2024)
The nutritional status of children under five years old is influenced by their food intake and maternal feeding behavior. Research shows that mothers who work longer hours tend to have children with poor nutritional intake. Maternal behavior in providing food role models also has a significant effect on children's nutritional status. This study aims to find out the influence of dietary recommendations on toddlers nutritional status in working mothers. This research is an analytical observational empirical research with a cross sectional design. The reachable population is all working mothers who have toddlers in D.I. Yogyakarta. Samples were taken by purposive sampling. The research sample was 211 mother-toddler pairs. Data was collected using self-administered offline and online questionnaires consisting of questionnaires on respondent characteristics (mothers and toddlers), and a questionnaire for food role models, namely Musher-Eizenman's Comprehensive Feeding Practices Questionnaire. The statistical test carried out was the Kruskall Wallis test. The majority of mothers are 30 years old and have worked for around 5 years and the average income received is around 2 million rupiah. Most mothers work as private sector workers, with the majority holding positions as employees. After measuring the nutritional status of toddlers, it was found that the majority (59%) of toddlers had good nutrition (n=124). %). The highest average food role model score in the eating model component was 3.97 ± 0.67). The relationship between the three components of the food role model and nutritional status was analyzed, eating model (X2(2) = 2.516, p-value = 0.2842), food education (X2(2) = 0.847, p-value = 0.6547), and overall (X2(2) = 2.165, p-value = 0.3388). It was found that food role model is not significantly related to nutritional status of toddlers.